Case Studies with Treatment Interventions among Ten Family Businesses in Istanbul - Tarhan, İbrahim Ethem (My University, 2012)
The primary purpose of this study was to present family businesses in Turkey as case studies as a way to describe the extent to which family members were aware of their family business dynamics and of any issues that interfered with their business processes. Also, the secondary purpose was to investigate the impact of two levels of a consultative relationship on awareness of family business problems in ten family businesses in Istanbul, Turkey. Moreover, the combined mixed-method research findings indicated that there were similarities between Turkish family businesses and Western family businesses as far as business family dynamics were concerned.
Keywords: Family Business; Conflict Resolution; Intensive Consultation; Intensive Consultation; Brief Consultation; Communication